The Influence of Private Brand and National Brand on Brand Loyalty with Perceived Quality as an Intervening Variable on Tissue Products in Soloraya - Putri Febriqa Khairun Nisa’; Moechammad Nasir (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of private label and national brands on brand loyalty for Indomaret tissue products in the Soloraya region, using perceived quality as a mediating variable. The research employs a quantitative method with primary data collected from 250 respondents through a closed-ended questionnaire. The analysis uses the Partial Least Squares (PLS) model to test relationships between variables. The findings reveal that private label and national brands significantly influence perceived quality, with private label brands showing a greater contribution. Perceived quality plays a crucial role in enhancing brand loyalty, both directly and as a mediator between brands and loyalty. Although national brands have a stronger direct impact on brand loyalty, private label brands also demonstrate potential in fostering loyalty through positive perceived quality. This study contributes to retail management by emphasizing the importance of perceived quality as a key factor in improving consumer loyalty. Future research is recommended to broaden the scope of products and regions to achieve more representative results.